miR-224-5p Carried by Human Umbilical Cord Mesenchymal Stem Cells-Derived Exosomes Regulates Autophagy in Breast Cancer Cells via HOXA5 - Wang, Yichao; Wang, Pan; Zhao, Lei; Chen, Xiaoying; Lin, Zhu; Zhang, Ling; Li, Zhaoyun (Frontiers in Cell and Developmental Biology, 2021)
Objective: In this study, we focused on the potential mechanism of miRNAs carried by human umbilical cord mesenchymal stem cells-derived exosomes (hUCMSCs-exo) in breast cancer (BC). Methods: RT-qPCR was conducted for the expression of miR-224-5p and HOXA5 in tissues and cells. After co-culture of exosomes and MCF-7 or MDA-MB-231 cells, the cell proliferation was observed by MTT and cell colony formation assay, while apoptosis was measured by flow cytometry. In addition, the expression of HOXA5 and autophagy pathway-related proteins LC3-II, Beclin-1 and P62 was detected by western blotting. And immunofluorescence was applied for detection of LC3 spots. The binding of miR-224-5p to HOXA5 was verified by the luciferase reporter gene assay and RNA-binding protein immunoprecipitation assay. Finally, in vivo experiment was performed to investigate the effect of miR-224-5p on BC growth. Results: MiR-224-5p was up-regulated and HOXA5 was down-regulated in BC tissues and cells. HOXA5 was confirmed to be the target gene of miR-224-5p. MiR-224-5p carried by hUCMSCs-exo was able to promote the proliferation and autophagy of BC cells, while inhibited apoptosis. Bases on xenograft models in nude mice, it was also revealed that miR-224-5p carried by hUCMSCs-exo could regulate autophagy and contribute to the occurrence and development of BC in vivo. Conclusion: MiR-224-5p carried by hUCMSCs-exo can regulate autophagy via inhibition of HOXA5, thus affecting the proliferation and apoptosis of BC cells.